Семантични особености на глаголния префикс ув родопските диалекти на българския език - Кочева, Ана (Gwary Dziś, 2022)
The issue of the semantic distinction between the two prefixes: у- and о- in the all-Bulgarian plan (literary language and dialects) is generally solved in the following manner: the prefix о-, originating from the old Bulgarian preposition о (об, обь) still denotes ‘touching the surface’ ‘or ‘ external coverage of an object’ while the prefix y- means ‘place of action’ or ‘action directed towards // or inside the object’, as well as ‘centrifugal action of an object’. In dialects, however, mostly for phonetic reasons, these basic meanings of prefixes often change. The situation is not the same even in the Rhodope dialects. In the northern (mostly Christian) dialects, the labial suffix (y-, o-) is more typical, in the south (mostly Bulgarian-Mohammedan) – of the non-labial type (ạ or a).